2018
DOI: 10.29333/ejgm/86194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroalcoholic extract of Cannabis (Cannabis sativa L.) on morphology and the process of human adipose-drived mesenchymal stem cell growth

Abstract: Background: Today, cannabis sativa L. is the most consuming drug trafficking plant in the world after nicotine and alcohol. Aims: Given the properties of cannabis and psychoactive compounds of this opiate drug, including hashish, as well as the importance of human adipose-derived mesenchymal stem cells in the restoration and regeneration of organs and its application in tissue transplantation and tissue engineering, the current paper investigates the effect of hashish (hydroalcoholic extract of cannabis) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Jamshidi et al showed an increase in apoptosis and a decrease in growth kinetics of human adiposedrived mesenchymal stem cells following cannabis use. 20,21 Our findings on inflammatory responses, degeneration and necrosis in adipose tissue following METH use are in agreement with these studies. Sazmand et al (2018) have also investigated the effect of cannabis on growth of bone marrow mesenchymal stem cells in rat and demonstrated an increase in apoptosis and a decrease in proliferation of stem cells identical to our results after the substance use.…”
Section: Discussionsupporting
confidence: 91%
“…Jamshidi et al showed an increase in apoptosis and a decrease in growth kinetics of human adiposedrived mesenchymal stem cells following cannabis use. 20,21 Our findings on inflammatory responses, degeneration and necrosis in adipose tissue following METH use are in agreement with these studies. Sazmand et al (2018) have also investigated the effect of cannabis on growth of bone marrow mesenchymal stem cells in rat and demonstrated an increase in apoptosis and a decrease in proliferation of stem cells identical to our results after the substance use.…”
Section: Discussionsupporting
confidence: 91%
“…The positive in vitro effect of Feijoa on cell viability and proliferation, membrane peroxidation, and disaccharidase in Caco-2 and HT-29 cells was reported before (11). Cellular apoptosis following substance use was previously reported showing an increase in Bax gene and death signaling cascade too (12,13).…”
Section: Discussionmentioning
confidence: 82%